Multi-Walled Carbon Nanotubes As Pervaporation Buckypaper Membranes And Catalysts For Etherification Reaction - Yee, Kian Fei (2016)
Asymmetric membranes were prepared by first forming multi-walled carbon nanotube-buckypaper (MWCNT-BP) structures as the pre-selective layer followed by coating the structures with a thin layer of polyvinyl alcohol (PVA) to form novel MWCNT-BP/PVA asymmetric membranes. The resultant asymmetric membranes were applied in the pervaporation process for dehydration of multi-component mixture obtained from an etherification reaction process. The pervaporation results revealed that the asymmetric membranes exhibited two- and four-fold enhancements of the water permeation flux and separation factor, respectively, compared to the pure PVA membrane. This effect was observed due to the hydrophilic group on the purified MWCNTs and the nanochannels of the pre-selective layer, which favour the permeation of water molecules. A solution-diffusion model of Rautenbach was adequately in describing the pervaporation process. In the etherification reaction process study, sulfonated MWCNTs catalyst containing Lewis acid sites was prepared via sulfonation process with sulfuric acid. The catalytic performances of sulfonated MWCNTs catalyst were investigated in the etherification reaction process of tert-butyl alcohol (TBA) with ethanol. The effect of process variables (reaction temperature, reaction time, molar ratio of ethanol to TBA, catalyst loading) on the conversion of TBA, selectivity of ethyl tert-butyl ether (ETBE) and yield of ETBE were investigated using two different approaches: conventional approach and response surface methodology (RSM) approach. In the conventional approach, the optimum reaction conditions consisted of 4 h of reaction time at 140 °C, a molar ratio of ethanol to TBA of 2:1 and a catalyst loading of 3 wt%. The optimum TBA conversion, ETBE selectivity and ETBE yield were 64 %, 68 % and 44 % respectively. On the other hand, the results obtained from RSM approach revealed that individual variables and their interactions affect the etherification reaction significantly. The 4 h reaction at 146 °C, molar ratio of ethanol to TBA of 2.17:1 and 3.26 wt% catalyst loading gave an optimum conversion of TBA of 72 %. Furthermore, the optimum selectivity and yield of ETBE were 60 % and 43 %, respectively. It was interesting to note that similar optimum process variables were obtained from both approaches. Nevertheless, RSM approach provides a better and specific optimum process variables since the values were predicted from model equations. An etherification mechanism was proposed to describe the etherification reaction. The sulfonated MWCNTs catalysts exhibited an insignificant dropped of the catalytic performance after four consecutive experimental runs and it was easily regained after regeneration. Subsequently, the optimized reaction mixture was applied as the feed solution for dehydration of water using the novel asymmetric membrane. The total permeation flux of approximately 7 g/m2∙h, and separation factor of approximately 400 were obtained.